PENGARUH TERAPI TANDEM WALKING EXERCISE TERHADAP PENINGKATAN KESEIMBANGAN UNTUK MENGURANGI RISIKO JATUH PADA LANSIA - Esti Nawang Rininingtyas; Pramono Giri Kriswoyo; Adi Isworo; Moh Hanafi (Jendela Inovasi Daerah, 2026)
The aging process leads to a decline in musculoskeletal and neuromuscular function, increasing the risk of falls among older adults. The World Health Organization (WHO) reports that approximately 28–35% of individuals aged ≥65 years experience falls annually, with prevalence in Indonesia ranging from 12–29%. One preventive strategy to reduce fall risk is Tandem Walking Exercise. This study aimed to analyze the effect of Tandem Walking Exercise on balance in older adults, measured using the Timed Up and Go Test (TUGT) as an indicator of fall risk. This study employed a pre-experimental design with a one-group pretest–posttest approach. The sample consisted of 33 older adults selected through purposive sampling in the working area of Bandongan Public Health Center, Magelang Regency. The intervention was conducted for one week with a total of three exercise sessions. Balance was assessed before and after the intervention using the TUGT. Data were analyzed using the Wilcoxon Signed Rank Test. The results showed a significant difference in TUGT scores before and after the intervention (p < 0.05), indicating improved balance and reduced fall risk among older adults. Tandem Walking Exercise has a significant effect on improving balance and can serve as an alternative preventive intervention in community settings. However, the generalizability of the findings is limited due to the absence of a control group, short intervention duration, and small sample size.